Interaction and Application of Molds and Yeasts in Chinese Fermented Foods - Yang, Qilin; Yao, Hongli; Liu, Shuangping; Mao, Jian (Frontiers in Microbiology, 2022)
Fermentation is an ancient food preservation and processing technology with a long history of thousands of years, that is still practiced all over the world. Fermented foods are usually defined as foods or beverages made by controlling the growth of microorganisms and the transformation of raw and auxiliary food components, which provide the human body with many beneficial nutrients or health factors. As fungus widely used in traditional Chinese fermented foods, molds and yeasts play an irreplaceable role in the formation of flavor substances and the production of functional components in fermented foods. The research progress of molds and yeasts in traditional Chinese fermented foods from traditional to modern is reviewed, including the research on the diversity, and population structure of molds and yeasts in fermented foods. The interaction between fermenting mold and yeast and the latest research results and application development prospects of related industries were discussed.